Identification and expression pattern analysis of the OsCBL gene family in rice - Hu, Zhao; Xie, Fengpu; Cai, Lu; Qian, Run (Frontiers in Plant Science, 2025)
Calcium (Ca2+) signaling, which is mediated by calcineurin B-like proteins (CBLs), plays a pivotal role in the way that plants respond to abiotic stresses. However, the systematic bioinformatics and expression pattern analysis of OsCBLs remain largely unknown. In this study, we conducted a thorough genome-wide analysis of the OsCBL gene family in rice, identifying ten members spanning six chromosomes. Phylogenetic analysis classified these genes into three subfamilies, revealing evolutionary conservation with Zea mays and Hordeum vulgare, while also highlighting lineage-specific expansions. Structural characterization revealed that all OsCBL proteins contain three conserved EF-hand domains, though variations in protein stability, subcellular localization and motif composition were observed, particularly with regard to the chloroplast localization of OsCBL4/8/9/10. Promoter analysis revealed distinct cis-elements linked to responses to abscisic acid, drought and light, suggesting functional diversification among the different members. Expression profiling revealed that OsCBL5 and OsCBL9 were specifically induced by heat but repressed by cold. In contrast, OsCBL3 responded to various stresses, including salt and temperature. Predictions of protein-protein interactions linked several OsCBLs to ion transporters. Notably, the functions of OsCBL1 and OsCBL9 may be exerted through the formation of a heterodimer. These findings provide critical insights into the functional divergence of OsCBL genes and lay the groundwork for future studies on calcium-mediated stress responses in rice.